1990
DOI: 10.1007/bf01541548
|View full text |Cite
|
Sign up to set email alerts
|

Effects of androgen treatment in impotent men with normal and low levels of free testosterone

Abstract: The relation between sexual function and serum free testosterone (fT) levels, which represent the active fraction of circulating testosterone, was evaluated. Two groups of impotent male subjects with mild hypogonadism were treated with oral testosterone undecanoate (TU); these men presented with tT/luteinizing hormone (LH) ratio and tT levels at the lower limits of normal. The first group had serum fT below 6.6 ng/ml, considered the lower normal value, according to our laboratory method, whereas the second gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(43 citation statements)
references
References 19 publications
1
39
0
Order By: Relevance
“…24,40 Owing to the relatively high age of the participants in our study, it is likely that there were more causes for erectile dysfunction than the low-normal testosterone concentrations alone, such as neurological causes, cardiovascular diseases (arterial insufficiency, venous leak) and depression. Testosterone replacement therapy alone will not correct these problems.…”
Section: Discussionmentioning
confidence: 91%
“…24,40 Owing to the relatively high age of the participants in our study, it is likely that there were more causes for erectile dysfunction than the low-normal testosterone concentrations alone, such as neurological causes, cardiovascular diseases (arterial insufficiency, venous leak) and depression. Testosterone replacement therapy alone will not correct these problems.…”
Section: Discussionmentioning
confidence: 91%
“…There was no demonstrable effect of testosterone on erectile function, and a clinically significant effect on desire in only 3 patients in the low-desire group. Carani et al 45 2), which measures the extent to which an individual seeks sexual stimuli. There was no effect on measures of sexual behavior, including intercourse frequency, erectile function, or masturbation and no apparent effect on mood.…”
Section: Non-depressed Men With Sexual Dysfunctionmentioning
confidence: 99%
“…The effects of androgens on libido and sexual behaviour is well established, 21 ± 23 but their effect on the erectile mechanism remains contraversal. 1,4,5,14 However, Aydin et al 20 reported that response to exogenous testosterone may be mediated by heightened libido, as well as the known antidepressant effect of androgens. These effects may contribute to the return of potency in patients with stational or psychogenic impotence and in patients with underlying endocrine abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…3 The causal relationship has not been established between hypogonadism and erectile dysfunction. 4,5 Also, the minimum level of testosterone needed to maintain the sexual function has not been established. 6 Although there is no ®rm evidence that testosterone supplementation results in enhancement of erectile function, 5 the National Institute of Health (NIH) consensus development panel on impotence proposed that for some patients with hypogonadism, androgen replacement therapy may sometimes be effective in improving erectile function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation